2012
DOI: 10.1074/jbc.m111.322644
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger Protein ZFP57 Requires Its Co-factor to Recruit DNA Methyltransferases and Maintains DNA Methylation Imprint in Embryonic Stem Cells via Its Transcriptional Repression Domain

Abstract: Background: ZFP57 is a maternal-zygotic effect gene that maintains genomic imprinting in mouse embryos. Results: KAP1 facilitates the interaction between ZFP57 and DNA methyltransferases. The KRAB box of ZFP57 is required for maintaining DNA methylation imprint in ES cells. Conclusion: ZFP57 recruits DNA methyltransferases and maintains DNA methylation imprint through KRAB box-mediated interaction.Significance: This work implies that ZFP57 recruits DNA methyltransferases via KAP1 to maintain DNA methylation im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
174
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(187 citation statements)
references
References 61 publications
13
174
0
Order By: Relevance
“…26 Several reports have suggested that this transcription factor binds to KRAB-associated protein 1 (KAP1), a scaffold protein for various heterochromatin-inducing factors, through its KRAB domain, and is involved in genome imprinting by recruiting KAP1 to several ICRs. 26,27,33 In addition, mutations in the ZFP57 gene result in transient neonatal diabetes mellitus type 1, possibly through Plagl1 overexpression. 34,35 The role of ZFP57 in tumorigenesis has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several reports have suggested that this transcription factor binds to KRAB-associated protein 1 (KAP1), a scaffold protein for various heterochromatin-inducing factors, through its KRAB domain, and is involved in genome imprinting by recruiting KAP1 to several ICRs. 26,27,33 In addition, mutations in the ZFP57 gene result in transient neonatal diabetes mellitus type 1, possibly through Plagl1 overexpression. 34,35 The role of ZFP57 in tumorigenesis has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…In murine embryonic stem cells, this protein is important for self-renewal (Hu et al 2009;Seki et al 2010). TRIM28 is also essential for the silencing of endogenous and some exogenous retroviruses in murine embryonic cells Goff 2007, 2009;Matsui et al 2010;Rowe et al 2010), where its KRAB-ZFP-mediated docking triggers the formation of heterochromatin, notably through the recruitment of SETDB1, the histone methyltransferase responsible for depositing the H3K9me3 repressive mark (Schultz et al 2002;Ivanov et al 2007;Frietze et al 2010), and of DNA methyltransferases, the action of which extends to adjacent CpG islands (Quenneville et al 2011(Quenneville et al , 2012Zuo et al 2012). A major consequence of the TRIM28-mediated repression of ERVs is the preservation of the transcription dynamics of murine ES cells, as repressive chromatin marks at murine ERVs are replaced upon Trim28 knockout by histone modifications typically found on active enhancers, which results in inducing the expression of nearby cellular genes, notably those harboring bivalent promoters (Rowe et al 2013b).…”
mentioning
confidence: 99%
“…If a particular CpG is demethylated under maternal-null circumstances, reexpressed paternal TRIM28 cannot be targeted to it and cannot restore DNA methylation. Similarly, reexpression of ZFP57 in Zfp57-deleted ES cells cannot restore methylation to sites that have lost it (Zuo et al 2012). Finally, this mode of interaction offers a plausible model for the noncanonical targeting of the dramatically reduced levels of DNMT1 to ICRs in preimplantation embryos; both maintenance DNAmethyltransferase and the de novo DNA-methyltransferases (DNMT3A/B) are bona fide interaction partners of TRIM28 (Quenneville et al 2011;Zuo et al 2012).…”
Section: The Trim28-complex Function In Genomic Imprintingmentioning
confidence: 94%
“…This multisubunit, heterochromatin-inducing molecular complex also serves as a platform for recruiting DNA methyltransferases, which can then induce and maintain DNA methylation in proximity to their target sites ( Fig. 2; Quenneville et al 2011;Zuo et al 2012).…”
Section: Trim28-a Multifaceted Worker In the Chromatin Fieldmentioning
confidence: 99%
See 1 more Smart Citation